2009
DOI: 10.1111/j.1745-4557.2009.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Bread Making of Durum Wheat With Chickpea Sourdough or Compressed Baker's Yeast

Abstract: Two ways of improving durum wheat bread-making quality were evaluated.First, durum wheat (cultivar "Papadakis") was blended with bread wheat flour of good (A-flour)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
(29 reference statements)
0
8
1
1
Order By: Relevance
“…In developing countries, there is growing research interest in fortifying wheat bread with processed legumes, especially fermented legume flour, to increase nutrient the intake of high‐quality protein and bioactive ingredients, and to take advantage of bread as a carrier of health‐promoting compounds (Shrivastava & Chakraborty, 2018). Though there are few reports on the inclusion of fermented legume flour in wheat‐based bread (Bourré et al., 2019; Hallén, Ibanoğlu, & Ainsworth, 2004; Kefalas et al., 2009; Rizzello, Calasso, Campanella, De Angelis, & Gobbetti, 2014; Shrivastava & Chakraborty, 2018), to the best of our knowledge, fermented African yam bean flour (FAYBF) as an ingredient in bread making has not been explored. Therefore, the objective of the study was to determine the effect of SSF on the functional properties, nutritional composition, and ANFs of AYB flour and to investigate the nutritional composition and the functional properties of the breads prepared from wheat‐FAYBF blends.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, there is growing research interest in fortifying wheat bread with processed legumes, especially fermented legume flour, to increase nutrient the intake of high‐quality protein and bioactive ingredients, and to take advantage of bread as a carrier of health‐promoting compounds (Shrivastava & Chakraborty, 2018). Though there are few reports on the inclusion of fermented legume flour in wheat‐based bread (Bourré et al., 2019; Hallén, Ibanoğlu, & Ainsworth, 2004; Kefalas et al., 2009; Rizzello, Calasso, Campanella, De Angelis, & Gobbetti, 2014; Shrivastava & Chakraborty, 2018), to the best of our knowledge, fermented African yam bean flour (FAYBF) as an ingredient in bread making has not been explored. Therefore, the objective of the study was to determine the effect of SSF on the functional properties, nutritional composition, and ANFs of AYB flour and to investigate the nutritional composition and the functional properties of the breads prepared from wheat‐FAYBF blends.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies concerning chickpea fermentation or bakery products produced with chickpea sourdough are very limited (Tulbek, 2006;Kefalas et al, 2009). Only few studies regarding the use of chickpea flour in cake (Gomez et al, 2008;Hera et al, 2012) or in breads (Rizzello et al, 2014a) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier work, Kefalas et al . () indicated that CIT makes gluten more inclined to strengthening. This effect may be closely associated with dough acidification during which hydrogen anions from acid bind to negative parts of amino acids, changing the total charge of protein macromolecule positive hence making it prone to strengthening (Galal et al .…”
Section: Introductionmentioning
confidence: 99%